Nernst equation applied to electrochemical systems and centenary of his Nobel Prize in chemistry - Ciribelli, Breno Nascimento; Colmati, Flavio; Souza, Elki Cristina de (International Journal for Innovation Education and Research, 2020)
Walther Hermann Nernst received the Nobel Prize in Chemistry in 1920 for the formulation of the third law of thermodynamics, thus celebrating a century in this 2020 year. His work helped the establishment of modern physical chemistry, since he researched into fields, such as thermodynamics and electrochemistry, in which the Nernst equation is included. This paper reports on several experiments that used a Daniell galvanic cell working in different electrolyte concentrations for comparing results with the theoretical values calculated by the Nernst equation. The concentration and activity coefficients values employed for zinc sulfate and copper electrolytes showed activity can replaces concentrations in thermodynamic functions, and the results are entirely consistent with experimental data. The experimental electromotive force from standard Daniell cell, for ZnSO4 and CuSO4, with unitary activity and in different concentrations at room temperature is in agreement with those from theoretical calculations. Cu2+ ion concentrations and temperature were simultaneously varied; however, the cell potential cannot be included in calculations of Nernst equation for different temperatures than 25 °C because the standard potential value was set at 25 °C. The cell potential decreases drastically when the Cu2+ concentration was reduced and the temperature was above 80 oC.